Gabby : a story of courage and hope - Giffords, Gabrielle D. (Gabrielle Dee), 1970-; Kelly, Mark E.; Zaslow, Jeffrey (New York, NY : Scribner, 2011)
Congresswoman Gabrielle Giffords and her husband, astronaut Mark Kelly, showed Americans how optimism, an adventurous spirit, and a call to service can help change the world. Their arrival in the spotlight came under the worst of circumstances. On January 8, 2011, while meeting with constituents in Tucson, Arizona, Gabby was the victim of an assassination attempt that left six people dead and thirteen wounded. Gabby was shot in the head; doctors called her survival "miraculous." As the nation grieved and sought to understand the attack, Gabby remained focused on her against-all-odds recovery.
Keywords: Giffords, Gabrielle D. -- 1970-; Kelly, Mark E; Giffords, Gabrielle D. -- 1970- -- Marriage; Giffords, Gabrielle D. -- 1970- -- Assassination attempt, 2011.; Giffords, Gabrielle D. -- 1970- -- Health; United States. -- Congress. -- House -- Biography; Women legislators -- United States -- Biography; Astronauts -- United States -- Biography; Head -- Wounds and injuries -- Patients -- Rehabilitation